Anak Jalanan dan Sebuah Subkultur Kehidupan Urban di Kota Makassar - Elsa Cahyani; Abdul Rahman (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
This study aims to determine (1) the process of the emergence of a punk community in the city of Makassar. This type of research is descriptive qualitative research. The approach that researchers use is the phenomenological approach. The phenomenological approach is an approach that seeks to understand the meaning of an event and its influence on humans and situations. Punk began to enter Makassar around the 90s. Punk entered Makassar along with the entry of punk music such as Rock N Roll music. However, its development is not as rapid as the development of punk children in the Yogyakarta area. At first, Punk entered and became known to Makassar youth or Makassar teenagers. Punk did not immediately show itself openly to the wider community but instead began to show their form of flow to teenagers in the city of Makassar so that many teenagers liked punk and wanted to be part of the community.